The use of vanadium to enhance localised corrosion resistance in 18% chromium ferritic stainless steel - Pistorius, Petrus Christiaan (University of Pretoria, 2013)
Dissertation (M Eng (Metallurgical Engineering))--University of Pretoria, 2007.